CO2 valorisation based on Fe3O4/FeO thermochemical redox reactions using concentrated solar energy. (2nd February 2012) - Abanades, Stéphane; Villafan‐Vidales, Isabel
SUMMARY The solar‐driven dissociation of CO2 by thermochemical looping via Fe3O4/FeO redox reactions is considered. The process recycles and upgrades CO2 to ultimately produce chemical synthetic fuels from high‐temperature solar heat and abundant feedstock as only inputs. The two‐step process encompasses the endothermic reduction of Fe3O4 to FeO and O2 using concentrated solar energy as the high‐temperature source for reaction enthalpy and the nonsolar exothermic oxidation of FeO with CO2 to generate CO. The resulting Fe3O4 is then recycled to the first step and carbon monoxide can be further processed to syngas and serve as the building block to synthesise various synfuels by catalytic processes. This study examines the thermodynamics and kinetics of the pertinent reactions. The high‐temperature thermal reduction of Fe3O4 is realised above the oxide melting point by using concentrated solar thermal power. The reactivity of the synthesised FeO‐rich material with CO2 at moderate temperature is then investigated by thermogravimetry. FeO conversion higher than 90% can be achieved with reaction rates depending on temperature, particle size and CO2 concentration. The solar‐produced nonstoichiometric FeO is more reactive with CO2 than commercial pure FeO. Activation energies of 57 and 68 kJ/mol are derived from a kinetic analysis of the CO2‐splitting reaction in the range of 600 °C to 800 °C with solar and commercial FeO, respectively. Copyright © 2012 John Wiley & Sons, Ltd.